(3eNJUQ jTJed Ydi QShe GdNdaGA hBOGH NOeJge hGdJMjI hGdSdGe Ydjges
(3ChdgG (B:s
(3GdMeO ddg ai GdbOQI hGdLdGd hHYO agPG eNJUQ jTJed Ydi QShe GdNdaGA hBOGH NOeJge hGdJMjg hGdSdGe Ydjge hbO LYdfG gPG GdcJGH ai KdGKI CHhGH s
(3BNQgG (B:s
(3bGd JYGdi (B:" (3gd jSJhi GdPjf jYedhf hGdPjf dG jYedhf EfeG jJRci ChdhG GdCdHGH (B" (3hgPG BNQ YfjfG Hg ef LeY gPG GdcJGH GdeNJUQ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(364(3O(B) s
Keywords: (3GdeLGejYs